English in Nepal: Attitudes Towards Nepali English or Other Varieties of English - Dewan, Shankar (Journal of NELTA Gandaki, 2022)
Since the emergence of varieties of English, varying debates and discussions about their formal features, functions, and roles have persisted worldwide. This quantitative survey research aims to identify the attitudes of Nepali speakers of English towards Nepali English (NE) and other varieties of English. Using the survey questionnaire, the researcher collected primary data through online and face-to-face modes from one hundred participants sampled randomly, out of which fifty participants were the English language teachers from different schools and community campuses and fifty participants were Master level students, including those students pursuing their Master level thesis from a community campus of Morang district. The participants’ attitudes were analyzed and interpreted in terms of intelligibility, nature of standard, identity, practicality, and acceptance. The study showed that most participants were positive towards NE and most of them responded that they can better understand English spoken by NE speakers than British English (BE) or American English (AE) native speakers. However, majority of them were not against BE or AE in terms of intelligibility, nature of standard, and practicality though they supported NE more.